МОДЕЛЮВАННЯ ФРАНЧАЙЗИНГОВИХ ПЛАТЕЖІВ У РЕСТОРАННОМУ БІЗНЕСІ: ОБЛІКОВО-АНАЛІТИЧНИЙ АСПЕКТ - Ivanenko, Valentyna (Zhytomyr Ivan Franko State University, 2024)
The article discusses franchising as an effective business model of restaurant business. The state and development of the franchise market in the world and in Ukraine is analyzed. The advantages of running a restaurant business under franchise conditions are given. It has been established that three main options for calculating the use of a franchise can be distinguished: payment of only a one-time lump sum as the price for the right to join the restaurant chain; systematic payment during the term of the contract in the form of a royalty at a fixed rate or as a certain percentage of the franchisee's turnover; combined payment, which includes a one-time payment at the beginning of the contract for connecting to the franchisor's corporate network and regular royalties during the contract period. It has been proven that franchise payments for both the franchisee and the franchisor are accounting objects, and for the franchisee they are the main expenses that form the tax base. Proposals are made regarding the method of accounting for franchise payments in the franchisee, depending on whether the cost of the franchise is known or not and on the method of making franchise payments. Variants of the moment of payment of franchise payments have been identified (at the beginning of the contract, periodically during the contract and at the end of the contract), which have different effects on the accounting of franchising operations, as well as on the formation of the tax base, which makes it possible to predict the outcome of the decision in the future. In order to determine the impact of franchise payments on taxation and accounting, their accounting was modeled, taking into account such factors as information on the fixation of the franchise value and the method of payment of the lump sum. Summarized results of modeling the influence of factor ratios on the tax burden and economic indicators of the franchisee's activity are given, taking into account the time factor.